Age and DNA methylation subgroup as potential independent risk factors for treatment stratification in children with atypical teratoid/rhabdoid tumors - Frühwald, Michael; Johann, Pascal-David; Kool, Marcel; Graf, Norbert (Neuro-Oncology, 2020)
AbstractBackground. Controversy exists as to what may be defined as standard of care (including markers for stratification) for patients with atypical teratoid
Advance Access date 28 December 2019
Gesehen am 09.02.2021